The Role of Gender Identity in Well-Being and Psychosexual Aspects - Ilias Kassaras; Panagiotis Kordoutis (Interpersona: An International Journal on Personal Relationships, 2025)
This study underscores the impact of individuals’ gender identity experiences on their well-being and psychosexuality, drawing data from a sample of 2907 adults in Greece. Utilizing the Gender Identity Scale, we collected responses to transcend the conventional “man – woman” binary. Employing Latent Class Analysis, we identified nine Gender Identity Groups based on participants' responses. The results revealed that those embracing a fluid gender identity demonstrated better well-being indicators compared to those rigidly identifying as “men” or “women”. Notably, individuals associating with a “woman” gender identity displayed the lowest well-being indicators. In terms of psychosexual aspects, those with a fluid gender identity reported heightened sexual assertiveness and satisfaction, while individuals identifying solely as “men” exhibited elevated sexual anxiety. Furthermore, the gender of the sexual partner interacted with different gender identity groups. These findings suggest a potential influence of internalized societal roles and expectations linked to man and woman conceptual constructs, exerting pressure to conform to established gender norms. Limitations are also discussed.